Provisional Agenda for the Twenty-Sixth Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Provisional Agenda Friday, October 12, 2012 Introductory Session Global Economic and Financial Prospects and Policies (11:30 a.m. - 12:45 pagesm.) Tokyo International Forum, Hall B5 Restricted Session Early Warning Exercise (2:30 pagesm. - 4:00 pagesm.) Imperial Hotel, Hikari Room Saturday, October 13, 2012 Restricted Breakfast Dialogue on Policy Challenges (8:00 a.m. - 9:30 a.m.) Imperial Hotel, Hikari Room Plenary Session 1. Opening Remarks by the Chair (10:00 a.m. - 1:00 pagesm.) Imperial Hotel, Fuji Room 2. Global Policy Agenda - Securing the recovery and anchoring the future. Issues facing the advanced economies, emerging markets, low-income countries, Arab countries in transition, and the role of the Fund - Strengthening IMF Governance. 2010 Quota and Governance reforms; Quota Formula Review 3. Approval of Press Communique Press Conference (1:30 pagesm.) Tokyo International Forum, Hall D7 ********** An Informal Gathering of World Economic Leaders, bringing together IMFC members and selected private sector, civil society and academic leaders, will be held on Friday, October 12 from 4:30 pagesm. to 6:00 pagesm. in the Hikari Room at the Imperial Hotel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Governance Reform; IMF Governance; PP